Effect of parent income, learning ways, motivation on student’s result study in SMK Solok regency - Misnaliza Musa; Yunia Wardi; Idris Idris (Fakultas Ilmu Pendidikan UNP)
This research purposes is to find how the effect of parent income, the way of learning and student motivation to the result of study for student accountant program at SMK in Solok regency. This is descriptive, quantitative research, this research was conducted at SMK in Solok regency which conducted accountant competency. Technique to analyze data is using path analysis. The result of analysis show that 1) The parent income has significant effect to the way of students in learning, 2)The parent income has significant effect to student’s motivation in learning, 3) the parent income and the way of learning have significant effect to the result of study, 5)Learning motivation does not have significant effect to the result of study.